Drug Release Study Of PLA Microspheres Loaded With Gentamicin - Hamat, Nur Afiqah (Universiti Sains Malaysia, 2017)
Poly(lactic acid) (PLA) microspheres were fabricated through emulsion and solvent evaporation (ESE) technique. PLA loaded with different concentration of gentamicin were immersed in 0.5M NaOH solutions for 48 hours. The concentration of gentamicin were used are 0.125 %, 0.25 % and 0.375 %. Treated PLA microspheres were investigated using several characterization methods including Fourier Transform InfraRed (FTIR), Scanning Electron Microscopy (SEM), Particle size analysis, Contact Angle and Ultraviolet (UV) visible spectroscopy. The peak of gentamicin was determined and confirmed by FTIR. The treated PLA microspheres has becomes rough and porous surface after surface hydrolysis treatment. SEM proved the surface morphology changes of surface modified PLA microspheres. The value of contact angle was less than 90° after surface hydrolysis treatment and confirmed the improved hydrophilicity properties of surface modified PLA microspheres. The percentage of encapsulation efficiency (% EE) of gentamicin within PLA microspheres was evaluated by using UV-vis spectroscopy. The results recorded that higher concentration of gentamicin, which is 0.375 % gentamicin has the higher encapsulation efficiency around 15.22 %. The drug release of gentamicin from PLA microspheres showed the burst-effect manner within first 8 hours. After that, the drug release rate was slow and sustained release for the remainder days monitoring period.